Risk factors for aquiring multidrug-resistant organisms in urinary tract infections: A systematic literature review - Justin Tenney; Nicholas Hudson; Hazar Alnifaidy; Justin Ting Cheung Li; Kathy Harriet Fung (Elsevier, 2018)
Background: This is the first review to analyze literature identifying risk factors for a multidrug-resistant urinary tract infection (MDR UTI). Risk factors for other infections involving multidrug-resistant organisms have been evaluated in other reviews, but they do not assess urinary tract infections. The purpose of this study is to collect currently published data to determine the most commonly and consistently identified risk factors for UTIs. Material and methods: For this study, 3 independent researchers searched PubMed, Embase, and Cochrane database from 1966 to February 2016 for articles identifying risk factors for MDR UTI. Results: A total of 25 studies including 31,284 patients with positive cultures provide evidence for 12 possible risk factors for MDR UTI . The most commonly identified risk factor was previous antibiotic usage as evidenced in 16 of the 20 studies that evaluated this possible risk factor. The time range utilized to define previous antibiotic usage ranged from 2 days to 365 days. Other risk factors with the strongest supporting data were urinary catheterization, previous hospitalization, and nursing home residence. Conclusion: We identified 12 different possible risk factors for a MDR UTI, however several risk factors have minimal or conflicting evidence. The definitions of the risk factors varied widely among the studies, and should be standardized for future studies. Keywords: Cystitis, Microbial drug resistance, Pyelonephritis, Risk factors, Systematic review, Urinary tract infection